USAHA BAGONG APES (Bawang Goreng Bandeng Asin Pedas) BERBASIS KEKAYAAN LOKAL DAERAH - Masfufah - - (INOTEKS : Jurnal Inovasi Ilmu Pengetahuan, Teknologi, dan Seni, 2022)
Indonesia's profitable local wealth in agriculture is the shallots commodity as a business of fried onions. The innovation of fried onion business raised the concept of the blue economy / marine economy with the addition of Fish Floss. The use of modern technology in processing helps improve product quality. This study aims to utilize technology to improve product storage power and analyze business prospects with BEP calculations.The use of spinner and vacuum technology can be a solution for business producers in the processing of fried onions and milkfish. The use of spinner by conventional industries can reduce the oil content of fried onions and milkfish floss so that the crispness of the product increases, besides that the vacuum process can keep the processed products still hygienic during packaging, distribution, and consumption.The study results show the business feasibility of shallots and milk fish processed by Bagong Apes with a capital of Rp. 8,500,000, BEP 41, B / C Ratio 1.47, ROI 0.474 and monthly sales of 130 packaging shows that the Bagong Apes Business has a prospect to be developed. Keywords:  fried onion, milkfish floss, spinner, vacuum